Oportunidade e ameaça identitária : representações sociais sobre a escola por crianças imigrantes haitianas na cidade de Cuiabá (MT) - Appolon, Ilgentche (2021)
ABSTRACT: This study is linked to the line of research Culture, Memory and Theories of Education and is part of the project entitled "The construction of social knowledge by children, study on children's experiences and meanings", developed by the Research Group on Child Psychology in the Graduate Program in Education of the Federal University of Mato Grosso, Cuiabá campus. The objective is to identify and understand the social representations about the school shared by Haitian children enrolled in Brazilian schools, in order to analyze aspects about their social insertion in the context of public schools in Cuiabá. The theoretical studies based on the Theory of Social Representations in their ontogenetic approach (MOSCOVICI, 2010; JODELET, 2001; CASTORINA, 2010; DUVEEN, 1994); on Intercultural Education, the studies of Walsh and Candau et al were important. (2009, 2008, 2011, 2012, 2014, 2016), in dialogue with reflections on the concept of otherness and race relations according to Oliveira (2010) and Abramowicz (2011). The notion of social and school insertion was delineated from the contributions of Cotinguiba and Pimentel (2014) and Rossetti-Ferreira, Amorim and Vittória (1996). Institutional racism, contemporary migration, more specifically Haitian migration, and its flows to Brazil and Cuiabá are presented based on the studies of Marín (2016, 2017), Baptiste, Fouchard and Charles (2015, 1971, 2020), Alexandre (2018); Demartini (2004, 2006, 2011) and Martuscelli (2015). Data collection was carried out in a public elementary school in Cuiabá, with a class of children between seven and ten years old. The methodology used was inspired by the qualitative approach of the ethnographic type, organized in two stages: 1) documental analysis of the School's Political-Pedagogical Project (PPP); 2) semi-structured interview with Haitian children. For the evaluation of the information, comprehensive analysis and thematic content analysis were used (BARDIN, 1977). In the documental analysis, it was possible to observe the existence of an educational idea aligned with values such as democracy, otherness and culture, diffuse assumptions announced from conceptual generalization and homogenizing movement that promotes the invisibility of the specificities of immigrant children. Based on school experiences in Haiti and Brazilian schools, the children interviewed characterized the latter as a place of: a) encounter with difference and with the stranger; b) infrastructure, opportunities and apprenticeships; c) helpless, prejudice and racism; d) impatience and little empathy; e) psychological coping and resistance strategies. The facilitating strategies of school insertion created by Haitian children involve: i) the bond with Haitian children who study in another class; ii) bond with Brazilian children, classified as reliable and respectful; iii) counseling of parents; iv) request for intervention of the pedagogical authority; v) anchoring in religious discourses and in the idea of Human Rights. The cultural categorization of physical differences appears as the first challenge for school insertion, which requires from the "me" strategies of psychic confrontation in the face of the ethnic frontier that is imposed. The physical and cultural differences, now named as skin color, hair and language, were announced as generating social exclusion.